Synodality: Possibilities and Challenges in the Syro-Malankara Church - Valliyattu, Joseph (Asian Horizons, 2025)
Malankara Syrian Catholic Church is one of the two Oriental Catholic Churches in India and much of the ideas of participatory governance proposed in the current ideal of synodality can be recovered from her own ancient traditions. Due to various factors in its historical and living context, the Church is still able to maintain a “family spirit” in much of its organizational make-up and has kept institutionalization to a minimum. Even before the call for synodality came up, as part of consolidating the juridical foundations of the Church various legal and practical measures which encourage a participatory outlook have been in place in this Church. All this, this article argues, has helped this small but vibrant community to keep alive the promise to be an oikumene of God, rather than a hierarchical machinery. The article goes on to identify some present-day challenges to this heritage, which are to be addressed through participatory listening and decision making.